2005
DOI: 10.1039/b417449f
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake on mineral dust and soot: A fundamental view of the hydrophilicity of atmospheric particles?

Abstract: The interaction of water vapour with mineral dust and soot surfaces has been studied in the temperature range 203 K < T < 298 K using a Knudsen cell reactor. For the uptake of water on mineral dust an initial uptake coefficient of gamma(ini) = (6.3 +/- 0.7) x 10(-2) independent of temperature has been determined. In contrast the desorption rate has been found to be strongly temperature dependent with desorption rate constants decreasing from 1 x 10(-3) at 265 K to 1 x 10(-4) at 223 K. In addition, relatively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
7
51
0
Order By: Relevance
“…The kinetics of adsorption accelerates as the amount of adsorbed water increases (Pruppacher and Klett, 1997), so it is expected that α c would decrease with particle size. The literature value of (6.3 ± 0.7) × 10 −2 determined for the water vapor uptake coefficient on mineral dust (Seisel et al, 2005) is in agreement with the inferred α c from the highest critical supersaturation (α c ∼ 0.065). The diversity of inferred uptake coefficients could also be related to the chemical heterogeneity between samples.…”
Section: Droplet Growth Kineticssupporting
confidence: 87%
“…The kinetics of adsorption accelerates as the amount of adsorbed water increases (Pruppacher and Klett, 1997), so it is expected that α c would decrease with particle size. The literature value of (6.3 ± 0.7) × 10 −2 determined for the water vapor uptake coefficient on mineral dust (Seisel et al, 2005) is in agreement with the inferred α c from the highest critical supersaturation (α c ∼ 0.065). The diversity of inferred uptake coefficients could also be related to the chemical heterogeneity between samples.…”
Section: Droplet Growth Kineticssupporting
confidence: 87%
“…This process is thought to significantly impact the formation of cirrus at low T (Barahona et al, 2010;Hoose et al, 2010;Möhler et al, 2006). Weakly wettable species like soot may also nucleate ice in this mode at higher T than required for cirrus formation, potentially impacting the formation of mixedphase clouds (Seisel et al, 2005). Currently only CNT provides sufficient detail to allow the calculation of J het over a wide range of conditions and is therefore used here to derivē ϕ for deposition ice nucleation.…”
Section: Heterogeneous Ice Nucleation In the Deposition Modementioning
confidence: 99%
“…The form of Z het , c 1,s , and β h depends on whether the ice germ grows by direct incorporation of water molecules from the vapor phase or they first adsorb onto the particle surface and then diffuse to the ice germ. The value of c 1,s is also strongly influenced by the formation of water monolayers on the particle surface (Määttänen et al, 2005;Seisel et al, 2005). Määttänen et al (2005) have shown that these factors may introduce up to a factor of two uncertainty in f f .…”
Section: Ice Nucleation Rate Coefficientmentioning
confidence: 99%
“…Insoluble atmospheric particles, like mineral dust and soot, can also act as efficient cloud condensation nuclei if they acquire some amount of deliquescent material, such as (NH 4 ) 2 SO 4 (e.g., Seisel et al, 2005). The threshold of nucleation substantially decreases when water interacts (adsorbs) onto slightly soluble particles giving rise to the process of adsorption activation (Sorjamaa and Laaksonen, 2007;Henson, 2007).…”
Section: Introductionmentioning
confidence: 99%